ACQUIRED VOCABULARY AND ITS CLASSIFICATION BY LEVEL OF ASSIMILATION - Olimov Khurshid (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the development derivative vocabulary in terms of the degree of its assimilation in English based on French mastered words.